TINGKAT APRESIASI PUISI SISWA SD KELAS V DI KABUPATEN MERAUKE DAN FAKTOR-FAKTOR YANG MEMENGARUHINYA - Sri Yono NFN (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2019)
The aim of this study is to determine poetry appreciation level of class 5th of elementary school students in Merauke Regency. This study includes a type of quantitative research using a descriptive approach. The research subjects of class 5th of elementary school students in Merauke Regency school year 2017/2018 consisting of 72 students from 12 schools. The technique of taking school sampling uses cluster sampling, while the technique of class sampling uses random (random) samples. The technique of collecting data uses a test of poetry appreciation level. Measurements are made through ranking which is done by calculating the percentage for a scale of four. The results showed that the poetry appreciation level of class 5th of elementary school students in Merauke Regency was still low with an average value of 49. It was also known, factors such as how to appreciate poetry, school status, and school location also influenced students' poetry appreciation rates.